ANALYSIS OF IMPLEMENTATION OF THE GOOD CORPORATE GOVERNANCE PT. BANK BNI SYARIAH BRANCH OF TASIKMALAYA - Lahuri, Setiawan Bin; Wibisono, Vina Fithriana (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2020)
PT. Bank BNI Syariah is one of the best Islamic bank, which obtained the best award as the most efficient bank and first ranked in the category of best good corporate governance report. So, this study aim to explore the extent of implementation good corporate governance in PT. Bank Syariah Branch Tasikmalaya. This study is a field research using inductive method and content analysis approach. Data collection is using primary and secondary data by observations, interviews, and documentation. The results indicate that PT. Bank Syariah Branch Tasikmalaya has implemented good corporate governance principle by well according the Islamic perspective. Described about it that bank has implemented “anti graft” accordance with al-Amanah-alJama>’ah-al-Hasanah as a slogan in doing work; al-Tawhi>d and al-Rida as the basis for forming personal caracter; every Dhuhur and Ashar prayer, the office is temporarily closed; Tarhib Ramadhan as routine program every June 19 by holding an MHQ competition.